Вплив на інноваційну активність щодо суб’єктів господарського використання природних ресурсів - Шаповалова, О. (НДІ ПЗІР НАПрН України, 2023)
Стаття присвячена дослідженню проблеми актуальності прояву інноваційної активності у залежності від наявності соціальної складової у підходах до обрання об’єкта/суб’єкта інвестування. Викладено результати вивчення досвіду правового забезпечення зростання економіки підприємств у способи, що є екологічно невиснажливими. Звітування про екологічно невиснажливі способи зростання економіки підприємств стає інформаційнокомунікативним інструментом для прояву ініціативи щодо інноваційної активності (запровадження новітніх технологій господарювання). Стан вивчення проблем правового забезпечення зростання економіки підприємств у способи, що є екологічно невиснажливими, характеризується вкрай низьким рівнем розробки понятійного підходу до тлумачення знань про синергічний ефект від взаємодії основних напрямів економічної, правової та екологічної політики України. Обґрунтовано два актуальні питання при розв’язанні проблеми впливу на інноваційну активність щодо суб’єктів господарського використання природних ресурсів: (1) обрання нетипового стимулу для прояву ініціативи інноваційної активності із зовні, а саме – орієнтація на її прояв у залежності від наявності соціальної складової у підходах до обрання об’єкта/суб’єкта інвестування; (2) визначення методології вибору критеріїв для гармонізації українського законодавства про використання природних ресурсів суб’єктів господарювання. Окреслено перспективи дослідження впливу на інноваційну активність щодо суб’єктів господарського використання природних ресурсів, а саме – конкретизація публічно-правового режиму таких об’єктів, як ґрунт, надра, вода та ін., внаслідок детального розмежування реалізації суверенітету України над територіально-господарськими системами. Problem setting. As a result of open Russian aggression and hostilities on the territory of Ukraine, significant amounts of Ukrainian land, water and underground sources, and other natural resources have been withdrawn from economic circulation. These circumstances have a significant impact on the state of operations and innovative behavior of entities that use natural resources. Therefore, mechanisms of investment, innovation and state support for both entire industries and individual business entities that are appropriate to these circumstances are in demand. Under the above conditions, the problem of introducing the latest management technologies as a factor of manifestation of the initiative of innovative activity from the outside, which is directed at the subjects of economic use of natural resources, is becoming relevant. Analysis of recent research and publications. S.V. Solodchenko’s dissertation argues that not only state control should contain a social component, but also non-state control. He summarizes foreign experience and positively assesses the system of reporting on sustainable development indicators. Y. Brairaktar substantiates the stages of formation of nonfinancial reporting of enterprises, I. Vasylchuk considers non-financial reporting as a tool for managing the sustainable development of corporations, T. Sikorska and O. Osadcha predict the ways and consequences of integrating non-financial indicators into the reporting of a business entity. Target of the research is to study the problems of harmonization of the provisions of legislation on the use of natural resources in the field of economic activity on the basis of economic and legal approaches in order to formalize the procedure for certifying by economic entities their contribution to improving or intending to improve in the future the economic, environmental and social situation, as well as the processes and trends of economic development at the local, regional and global levels. Article’s main body. The modern system of reporting on sustainability indicators was developed by the Global Reporting Initiative (GRI) and was positively received by representatives of big business, transnational campaigns, nongovernmental organizations, investors, regulatory organizations and others. The article is devoted to the study of the issue of relevance of innovation activity depending on the presence of a social component in the approaches to the selection of an investment object/subject. The author presents the results of studying the experience of legal support for the growth of the economy of enterprises in ways that are environmentally sustainable. Reporting on environmentally sustainable ways of economic growth of enterprises becomes an information and communication tool for taking the initiative for innovation activity (introduction of the latest management technologies). The current state of research into the issues of legal support for the growth of the enterprise economy in environmentally sustainable ways is characterized by an extremely low level of development of a conceptual approach to the interpretation of knowledge about the synergistic effect of the interaction of the main directions of economic, legal and environmental policy of Ukraine. The author substantiates two topical issues in solving the problem of influence on innovation activity in relation to economic entities using natural resources: (1) selection of an atypical incentive for manifestation of the initiative of innovation activity from the outside, namely, orientation towards its manifestation depending on the presence of a social component in the approaches to the selection of an investment object/subject; (2) determination of the methodology for selecting criteria for harmonization of Ukrainian legislation on the use of natural resources by economic entities. The author outlines the prospects for studying the impact on innovation activity in relation to economic entities using natural resources, namely, specification of the public law regime of such objects as soil, subsoil, water, etc. as a result of a detailed delineation of the exercise of Ukraine’s sovereignty over territorial and economic systems. Conclusions and prospects for the development. It should be considered a high degree of evolution of the consciousness of investors who choose to invest their capital in those companies that report on environmentally sustainable ways of growing the economy of their enterprises. The public manifestation of innovative activity, depending on the presence of a social component in approaches to the selection of an investment object/subject, needs to be popularized in Ukraine. The tendency to cover non-financial macro-level indicators in the reporting of a business entity affects the growth of ratings of organizations that evaluate their activities by environmental, social and governance indicators when selected by investors.
Keywords: стимулювання інноваційної активності; екологічно невиснажливе господарювання; нефінансова звітність підприємств; публічно-правовий режим; господарсько-правове забезпечення; використання природних ресурсів; суб’єкти господарювання; environmental, social and governance indicators (ESG); business entities; stimulation of innovation activity; environmentally sustainable management; non-financial reporting of enterprises; public law regime; economic and legal support; use of natural resources